Legal Analysis of Debt Collector Case Settlement Through Restorative Justice at The Police Level - Kevin Maisyan Rizaldi Mendrofa; Ismaidar Ismaidar; Abdul Rahman Maulana Siregar (Journal of Research in Social Science and Humanities, 2025)
Debt collection practices by debt collectors in the consumer finance industry often raise legal issues, particularly when carried out through intimidation, threats, or the seizure of collateral without proper legal procedures. This situation causes the civil legal relationship between the debtor and the financing company to develop into a criminal case requiring law enforcement. In police practice, the resolution of such cases is often directed through restorative justice mechanisms as an alternative to criminal cases, as long as they comply with the provisions stipulated in the Republic of Indonesia National Police Regulation Number 8 of 2021. This study aims to analyze the legal aspects of the application of restorative justice in resolving debt collector cases at the police level and examine the position and responsibility of leasing companies regarding the actions of authorized debt collectors. The research method used is normative juridical with a statutory, conceptual, and case-based approach. The results show that restorative justice can only be applied to debt collector cases that are minor in nature, do not cause serious injuries, and the losses can be recovered through an agreement between the parties. Furthermore, the leasing company remains legally responsible for the actions of debt collectors as its extension, both in civil and criminal aspects. Therefore, the implementation of restorative justice must be carried out proportionally and still ensure legal protection for victims